The chemistry of MIL-125 based materials: Structure, synthesis, modification strategies and photocatalytic applications. Issue 1 (February 2022) - Abdul Mubarak, Nur Shazwani; Foo, K.Y.; Schneider, Raphaël; Abdelhameed, Reda M.; Sabar, S.
Abstract: Titanium-based metal-organic framework (Ti-MOF) is part of the MOF family and has attracted much interest for its unique structural features. Some Ti-based MOFs are difficult to crystallize during the synthesis process; hence only limited studies have been reported. Moreover, the fundamental of Ti-MOF has received less attention, which is crucial to the provision of scientific information for customizing Ti-MOF with suitable properties for practical applications. Thus, this review highlights the Ti-based MOF structure and subsequently summarizes the discovery and development of ever-emerging MIL-125 as advanced materials with multifunctional properties. MIL-125 is a Ti-based MOF derived from Ti metal ions and carboxylate organic ligands. Different modification strategies have been outlined, such as functionalizing with ligands, modifying with metal ions, or incorporating other materials. The versatility and flexibility of MIL-125 elevate its prospects in photocatalytic applications, such as photodegradation of water pollutants, water splitting, and photoreduction of CO2 . Finally, the future perspectives were presented at the end of this review to provide beneficial information aiming to expand the capability of MIL-125 in advanced chemistry and materials. Graphical Abstract: ga1 Highlights: Structural design and recent development of MIL-125 based MOF are summarized. Synthesis and modification of MIL-125 from different approach are discussed. Photocatalytic applications of MIL-125 based materials are explored.